Recent Geopolitical Transformations in the Islamic World: the Arab Spring - Bomfim, Nizete Maria (2018)
This article aims to analyze recent geopolitical changes in the Islamic world, caused by the so-called Arab Spring, initiated in 2011 when a protest in Tunisia triggered a revolt in Islamic countries against totalitarian regimes, in the guise of theocratic democracies, and where repression was tonic, disguised as religion and supported by it, although there were no records on religious grounds to do so. This fact reinforces our thesis that the great mass of the people can be manipulated by the powerful through religion.